How classical music is embedded in a cultural public sphere? (Música Hodie, 2018)
Classical music as a special form of culture has been widely defined within an ideological and social sphere in people’s everyday life. A particular form of power structure has encouraged individual musicians or music events organisers to re-think the relationship between the governmental structure and individual agencies within the local music sphere. It has become clear that musical exercise is not simply invented by individual musicians or individual music organisations, but through their political cultural sphere and through society. This paper discusses the nature of democracy over classical music and explores classical music in the context of cultural public sphere by theoretically reflecting the notion of public sphere by Habermas, and argues that the policy for classical music is all about bringing democracy to the local public, but, on the other hand, the local public still have concerns on whether local government really takes the necessary steps to make democracy widely available for all forms of music organisations and for everybody in the cultural sphere. The papers also discusses how the culture democracy exercise at a local music level, and explores that music education policy system together with an effective musical education curriculum should also play a positive role in addressing such concerns.